Public administration bodies in the sphere of health protection of Ukraine - Pravylo О. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to study the current state of the activities of state bodies, which, according to their functional powers, are called to ensure the fulfillment of state tasks in the field of health care of Ukraine. Methodology. The methodology includes a comprehensive analysis and generalization of the available scientific and theoretical material and the formulation of relevant conclusions and recommendations. During the research, the following methods of scientific knowledge were used: logical-semantic, comparative-legal, system-structural and statistical, analysis and synthesis. The results. In the process of research, the system of public administration bodies in the sphere of health care of Ukraine is outlined. The author emphasizes that among a significant number of public and private law bodies which are designed to ensure the realization of the right of citizens to healthcare in Ukraine, the key subjects of administrative and legal regulation of relations in the healthcare sector are executive authorities and their officials. Without diminishing the role of private law entities, it is worth emphasizing that it is the executive authorities, as public law entities, which are entrusted with the main tasks of ensuring and practical implementation of administrative and legal regulation of the citizen’s right to healthcare. The author emphasizes that a significant number of subjects of administrative law can be attributed to public administration bodies in the field of healthcare in Ukraine. The author emphasizes that in the doctrine of administrative law, in addition to the category of “public administration”, such categories as “public management” and “public administration” are used, and there are also different points of view regarding their definition and correlation. The author analyzes the scientific opinions on the category of “public administration” and the activities of public administration entities in the healthcare sector. Bodies of special sectoral competence have been established, as well as the fact that the State Service of Ukraine for Food Safety and Consumer Protection is an interdisciplinary subject of public administration in the field of health care. Practical significance. The results of the study can be used in the scientific and research field – as a basis for further research related to the improvement of the activities of public administration bodies in the field of health care, in law enforcement activities – to improve the practical activities of subjects ensuring the implementation of the right to health care.